Forward guidance at the zero lower bound in a model of price-level targeting - Gerhard Illing; Thomas Siemsen (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
We study monetary policy at the ZLB in a traceable three-period model, in which price-level targeting emerges endogenously in the welfare function. We characterize optimal price-level forward guidance under discretion and commitment. Potentially non-monotonic discretionary welfare losses are lowest with perfectly exible prices. Price-level targeting introduces a new constraint on optimal forward guidance that restricts the credible amount of overshooting. With this constraint, the zero lower bound may be binding even after the shock has abated. We characterize conditions when the commitment to hold nominal rates at zero for an extended period is optimal. Finally, we introduce government spending and show that under persistently low policy rates optimal government spending becomes more front-loaded, while procyclical austerity fares worse than discretionary government spending.
urn:nbn:de:bvb:19-epub-22797-0
Keywords: E43; E52; E58; 330; zero lower bound; forward guidance; price-level target; optimal policy